2012
DOI: 10.4067/s0717-95022012000200017
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Stomach Growth in the Human Fetal Period: a Postmortem Study

Abstract: SUMMARY:The aim of this work was to analyze the stomach growth rate, variability of proportion and shape during prenatal period, as well as evaluation of final features differentiation process distinctive for perinatal period. It seems interesting to compare stomach growth analyzed in situ on post-mortem fetuses with results obtained by other authors evaluating this process in sonographic examinations. Research was conducted on 225 post-mortem fetuses 12th to 40 th week of fetal age. There were measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…These findings were the findings of other workers in Table No. 14. This showed that the increase in weight of stomach substantially matched with findings provided by Gworys B et al 6…”
Section: Weight Of Foetal Stomachsupporting
confidence: 89%
“…These findings were the findings of other workers in Table No. 14. This showed that the increase in weight of stomach substantially matched with findings provided by Gworys B et al 6…”
Section: Weight Of Foetal Stomachsupporting
confidence: 89%